Assessment of Serum Hyaluronic acid and Ferritin levels in children with Acute Lymphoblastic Leukemia - Ula Abbas Jawdat; Maysem Mouayad Alwash (Iraqi Journal of Cancer and Medical Genetics, 2021)
Background: Acute lymphoblastic leukaemia is the most common form of cancer (25–30%) and predominant subtype of leukaemia (75–80%) in children. It represents a malignant expansion of immature lymphoid cells that results from multi-step genetic changes in a single lymphoid progenitor cell. Hyaluronic acid is a nonsulfated glycosaminoglycan. It is found mainly in the extracellular matrix (ECM), especially of the loose connective tissue, including the bone marrow. HA influences many processes such as angiogenesis and the growth and migration of cells. HA levels are elevated in various cancers including AML, lung and breast cancers but their prognostic significance is unclear. Ferritin is the primary iron storage protein. High concentrations of ferritin are found in the cytoplasm of the reticuloendothelial system;the liver, spleen and bone marrow. It is also found in extracellular compartments, such as the serum. Serum ferritin is significantly affected by acute and chronic inflammation and is frequently increased at diagnosis in several cancers. The aim was to to evaluate the level of serum hyaluronicacid and ferritin in patients with ALL at diagnosis and in remmision, to correlate with hematological,biochemical and clinical parameters and to investigate if serum HA and ferritin could have a prognostic impact on disease development. Materialsand Methods: A total of 60 subjects were enrolled in this study, 40 patients of ALL as cases (20 patients at diagnosis before starting chemotherapy and 20 patients in remission but still under therapy); and 20 age and gender-matched healthy subjects as controls. Serum HA was measured using a commercially available sandwich ELISA kit while serum ferritin was measured by immunoassay using an automated clinical chemistry analyzer. Results: Serum HA in newly diagnosed patients with ALL was significantly higher than either patients in remission or controls which suggests that HA could have a role in the malignant process of ALL.